Poziom wiedzy i zachowania zdrowotne studentek Uniwersytetu Medycznego w zakresie profilaktyki raka szyjki macicy = The level of knowledge and health behaviours of Medical University students in the area of cervical cancer prevention - Gawron, Żaneta; Natalia, Gajewska; Gujska, Dominika; Gutek, Anastazja; Szadowska-Szlachetka, Zdzisława; Rząca, Marcin (Journal of Education, Health and Sport, 2016)
Gawron Żaneta, Gajewska Natalia, Gujska Dominika, Gutek Anastazja, Szadowska-Szlachetka Zdzisława, Rząca Marcin. Poziom wiedzy i zachowania zdrowotne studentek Uniwersytetu Medycznego w zakresie profilaktyki raka szyjki macicy = The level of knowledge and health behaviours of Medical University students in the area of cervical cancer prevention. Journal of Education, Health and Sport. 2016;6(8):41-53. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59706 http://ojs.ukw.edu.pl/index.php/johs/article/view/3726 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. Poziom wiedzy i zachowania zdrowotne studentek Uniwersytetu Medycznego w zakresie profilaktyki raka szyjki macicy The level of knowledge and health behaviours of Medical University students in the area of cervical cancer prevention 1, 3Żaneta Gawron, 1, 2Natalia Gajewska, 1Dominika Gujska, 1Anastazja Gutek, 4Zdzisława Szadowska-Szlachetka, 4Marcin Rząca 1, 3Zaneta Gawron, 1, 2Natalia Gajewska, 1Dominika Gujska, 1Anastazja Gutek, 4Zdzislawa Szadowska-Szlachetka, 4Marcin Rzaca 1Studenckie Koło Naukowe, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie Students scientific association, Chair of Oncology and Enviromental Health, Medical University of Lublin 2Oddział Hematologii, Onkologii i Transplantologii Dziecięcej, Uniwersytecki Szpital Dziecięcy w Lublinie University Children’s Hospital in Lublin, Department: of Hematology , Oncology and Transplantation Children 3Oddział Otolaryngologii Dziecięcej, Foniatrii i Audiologii, Uniwersytecki Szpital Dziecięcy w Lublinie, University Children’s Hospital in Lublin. Department of Pediatric Otolaryngology , Audiology and Phoniatrics 4Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie Department of Oncology, Chair of Oncology and Enviromental Health, Medical University of Lublin Słowa kluczowe: rak szyjki macicy, studenci, czynniki ryzyka, objawy, profilaktyka wtórna nowotworów. Key words: cervical cancer, university students, risk factors, symptoms, secondary cancer prevention. Abstrakt Wstęp: Rak szyjki macicy na początku przebiega bezobjawowo a jego wczesne wykrycie dzięki udziałowi w programie wczesnego wykrywania w ramach profilaktyki wtórnej umożliwia skuteczne leczenie. Ważne jest, aby młode kobiety posiadały wiedzę na temat profilaktyki raka szyjki macicy i znały konsekwencje związane z niewykonywaniem badań przesiewowych. Celem badań było zbadanie poziomu wiedzy i zachowań zdrowotnych studentek uczelni medycznych w zakresie profilaktyki raka szyjki macicy. Materiał i metody: Badania przeprowadzono wśród 110 studentek pielęgniarstwa i fizjoterapii na drugim stopniu kształcenia Uniwersytetu Medycznego w Lublinie. Ich wiek mieścił się w zakresie 21- 40 lat. Narzędzie badawcze stanowił autorski kwestionariusz ankiety. Wyniki badań poddano analizie statystycznej przy pomocy programu StatSoft Statistica 10.0 PL. Wyniki: Najczęściej wskazywanymi czynnikami ryzyka zwiększającymi prawdopodobieństwo zachorowania na raka szyjki macicy były: duża liczba partnerów seksualnych (96%), przewlekłe zakażenia wirusem HPV (94%), wczesny wiek inicjacji seksualnej (84) oraz częste i nieleczone stany zapalne pochwy (76%). Najczęściej wskazywanym objawem raka szyjki macicy było krwawienie, które pojawia się pomiędzy regularnymi krwawieniami miesięcznymi (85%). Połowa badanych zadeklarowała, że w przyszłości nie weźmie udziału w badaniach przesiewowych wczesnego wykrywania raka szyjki macicy. Wnioski: Młode kobiety posiadają podstawową wiedzę dotyczącą profilaktyki raka szyjki macicy, ale nie zawsze przekłada się ona na pozytywne zachowania zdrowotne. Należy podjąć zadania na rzecz zwiększenia zgłaszalności na badania przesiewowe wykrywające raka szyjki macicy. W badaniach przesiewowych rzadziej biorą udział mieszkanki wsi oraz kobiety z niskim statusem socjoekonomicznym. Abstract Introduction: Cervical cancer is asymptomatic in its initial stages and its early detection due to participation in an early detection programme as part of secondary prevention enables its effective treatment. It is important for young women to be familiar with cervical cancer prevention and be aware of the consequences of failing to perform the screening tests. The objective of the study was to determine the level of knowledge and health behaviours of medical students in terms of cervical cancer prevention. Material and methods: The survey was conducted among 110 students of nursing and physiotherapy during their Master’s degree studies at the Medical University of Lublin. The age of the respondents was from 21 to 40 years. A self-designed questionnaire was used as the research tool. The results were subjected to statistical analysis with the use of the StatSoft Statistica 10.0 PL software. Results: The most frequently mentioned risk factors increasing the probability of cervical cancer were: a large number of sexual partners (96%), chronic HPV infections (94%), early sexual initiation (84%) and frequent untreated vaginal inflammations (76%). The most often identified symptom of cervical cancer was bleeding between regular monthly periods (85%). Half of the surveyed claimed that in the future they would not participate in screening tests for early cervical cancer detection. Conclusions: Young women have the basic knowledge on cervical cancer prevention but it does not always translate into positive health behaviours. Measures should be taken to increase the reportability for cervical cancer screening tests. Such tests are less often attended by women living in rural areas and those with a low socio-economic status.